2020
DOI: 10.36453/2318-5104.2020.v18.n3.p37
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre percepção subjetiva do esforço e fadiga neuromuscular dos membros inferiores em atletas de futebol

Abstract: OBJETIVO: Determinar a correlação entre a percepção subjetiva do esforço (PSE) e a fadiga neuromuscular dos membros inferiores por meio de saltos mensurados no pré e pós treino em atletas de futebol.MÉTODOS: Quatorze atletas de futebol (sub 17) foram monitorados ao longo de quatro sessões de treinamento. Com as seguintes características: estatura (173±6,81cm), peso (64,43±5,80kg) e percentual de gordura (14,74±3,11). A PSE foi monitorada por meio do aplicativo e-trimp, 15 minutos após o final de cada sessão de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…It should be noted that these studies on the RPE take a stand on plyometric intensity without any means of comparison (EMG, RSI, or force platforms). This is of concern, given that previous research (Müller et al, 2020) has found a weak relationship between RPE and reactive jumps power. Therefore, there is a need for further studies assessing the reliability and validity of the RPE for determining plyometric intensity.…”
Section: General Discussion On Plyometric Intensitymentioning
confidence: 89%
“…It should be noted that these studies on the RPE take a stand on plyometric intensity without any means of comparison (EMG, RSI, or force platforms). This is of concern, given that previous research (Müller et al, 2020) has found a weak relationship between RPE and reactive jumps power. Therefore, there is a need for further studies assessing the reliability and validity of the RPE for determining plyometric intensity.…”
Section: General Discussion On Plyometric Intensitymentioning
confidence: 89%